Improving Human Health in China Through Alternative Energy - Scott, Melissa; Sander, Robert; Nemet, Gregory; Patz, Jonathan (Frontiers in Public Health, 2021)
In this study, we estimate the health benefits of more stringent alternative energy goals and the costs of reducing coal-fired power plant pollution in China projected in 2030. One of our two overarching alternative energy goals was to estimate the health benefits of complete elimination of coal energy, supplemented by natural gas and renewables. The second was a policy scenario similar to the U.S. 2013 Climate Action Plan (CAP), which played a pivotal role leading up to the 2015 Paris Climate Agreement. We used the Greenhouse Gas and Air Pollution Interactions and Synergies (GAINS) model created by the International Institute for Applied Systems Analysis for our model simulations. We found that 17,137–24,220 premature deaths can be avoided if coal energy is completely replaced by alternative energy, and 8,693–9,281 premature deaths can be avoided if coal energy is replaced by alternatives in a CAP-like scenario. A CAP-like scenario using emission-controls in coal plants costs 11–18 per person. Reducing coal energy in China under a CAP-like scenario would free up 9.4 billion in the annual energy budget to spend on alternatives, whereas eliminating the cost of coal energy frees up 32 billion. This study's estimates show that more stringent alternative energy targets in China are worth the investment in terms of health.